Accounts Receivable Accounting System - Nabila Putriana; Yusri Hazmi; Siti Masyittah Fatar; Novi Rahmawani (West Science Accounting and Finance, 2024)
This article discusses the accounts receivable accounting system. The receivables accounting system aims to record mutations in the company's receivables from each debtor, which occur due to credit sales transactions, sales returns, cash receipts from receivables, and write-offs of receivables. In this research, the library research method was used, collecting data by searching for sources and constructing them from various sources such as books, journals and existing research. The result is that qualitative research is carried out with a research design where the findings are not obtained through statistical procedures or in the form of calculations, but rather aims to reveal phenomena holistically-contextually by collecting data from natural settings and using researchers as key instruments. It is hoped that this research can help future researchers and companies pay attention to the accounts receivable accounting system as a whole regarding the weaknesses of the current system so that they can overcome possible irregularities and make improvements in order to increase company value for the company's progress in the future.